1988
DOI: 10.1144/gsl.sp.1988.039.01.28
|View full text |Cite
|
Sign up to set email alerts
|

Syn- and post-rift igneous activity in the Porcupine Seabight Basin and adjacent continental margin W of Ireland

Abstract: Summary An igneous province in the Porcupine Seabight Basin and adjacent shelf region W of Ireland records repeated episodes of intrusive and extrusive igneous activity, from the mid-Jurassic to late Oligocene. The ‘Province’ maintains a regionally distinctive NE-SW and NNW-SSE curvilinear trend that is inherent to the basement. Mid-Jurassic pyroclastic airfall deposits were probably contemporaneous with mid-Kimmerian uplift. Voluminous early Cretaceous volcanism was coeval with an episode of rifting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 25 publications
2
52
0
Order By: Relevance
“…4a at rifting rates appropriate for the Porcupine Basin [Reston et al, 2004], especially in the absence of 247 voluminous syn-rift magmatism [Tate & Dobson, 1988] to advect heat. 248…”
Section: Results 179mentioning
confidence: 99%
“…4a at rifting rates appropriate for the Porcupine Basin [Reston et al, 2004], especially in the absence of 247 voluminous syn-rift magmatism [Tate & Dobson, 1988] to advect heat. 248…”
Section: Results 179mentioning
confidence: 99%
“…This was succeeded by a tectonically quiescent, post-rift period interrupted locally in the Porcupine, Slyne and Erris basins by an AptianAlbian rift phase. Early Cretaceous volcanism is suggested in the central part of the Porcupine Basin (Croker & Shannon 1987;Tate & Dobson 1988;Naylor et al 1999) (Fig. 15b, c).…”
Section: Stratigraphymentioning
confidence: 95%
“…Lower Cretaceous extrusives and tuffs occur through the Barremian-Albian succession (Tate & Dobson 1988;Naylor et al 2002). The Cenomanian -Danian chalk sequence in the Porcupine Basin ranges from 400 m near the margins of the basin to more than 1000 m in the basin centre (Moore & Shannon 1995).…”
Section: Stratigraphymentioning
confidence: 99%
“…The axial region of the central and northern parts of the Porcupine Basin is transected by a combination of the arcuate, deeply buried Porcupine Volcanic Ridge System and the N-trending Porcupine Arch , enclosure 1). The ridge system is considered by Tate and Dobson (1988) to represent an igneous complex of mainly Cretaceous age, although Reston et al (2001) prefer a serpentinite diapiric origin. The Porcupine Arch is a high-amplitude reflector which may mark the top of the crystalline basement or partially serpentinized mantle (Reston et al, 2004).…”
Section: Porcupine Basinmentioning
confidence: 99%
“…The ridges are considered to be extrusive volcanic edifices which were subsequently draped with sedimentary rocks until finally being overstepped by sediment in Eocene time (Scrutton and Bentley, 1988). The stratigraphic control does not allow them to be dated accurately but they may be of Early Cretaceous age, when there was also significant igneous activity in the Porcupine Basin and on the Labrador Margin (Scrutton and Bentley, 1988;Tate and Dobson, 1988;Balkwill, 1987;DeSilva, 1999). Although the seismically-imaged ridges appear extrusive, modelling by Scrutton and Bentley (1988) indicated that the magnetic anomalies are best explained by a combination of the extrusive units and underlying intrusions, presumably lying along the fissures through which the igneous rocks were emplaced.…”
Section: Rockall Basinmentioning
confidence: 99%